2023
DOI: 10.1093/mnras/stad2070
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of AGN in galaxies with different stellar population ages

Abstract: It has been argued that recycled gas from stellar mass loss in galaxies might serve as an important fuelling source for black holes (BHs) in their centers. Utilizing spectroscopic samples of galaxies from the Sloan Digital Sky Survey (SDSS) at z = 0–0.35 and the Large Early Galaxy Astrophysics Census (LEGA-C) survey at z = 0.6–1 that have X-ray coverage from XMM-Newton or Chandra, we test this stellar mass loss fuelling scenario by investigating how AGN activity and BH growth vary with the break strength at 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Riffel et al (2022Riffel et al ( , 2023 found a correlation of intermediate stellar population with AGN luminosity, which is interpreted as the recycled material from the intermediate-age stellar population triggering the AGN. Ni et al (2023) recently showed that a higher level of AGN activity is observed in galaxies with younger stellar population ages, where more recycled gas is produced. Consistent with these observational findings, our study highlights the substantial contribution of recycled gas in triggering AGNs within a comprehensive cosmological hydrodynamic simulation.…”
Section: The Importance Of Recycled Gasmentioning
confidence: 99%
“…Riffel et al (2022Riffel et al ( , 2023 found a correlation of intermediate stellar population with AGN luminosity, which is interpreted as the recycled material from the intermediate-age stellar population triggering the AGN. Ni et al (2023) recently showed that a higher level of AGN activity is observed in galaxies with younger stellar population ages, where more recycled gas is produced. Consistent with these observational findings, our study highlights the substantial contribution of recycled gas in triggering AGNs within a comprehensive cosmological hydrodynamic simulation.…”
Section: The Importance Of Recycled Gasmentioning
confidence: 99%